2007
DOI: 10.1163/22941932-90001633
|View full text |Cite
|
Sign up to set email alerts
|

Within Tree Variation of Lignin, Extractives, and Microfibril Angle Coupled With the Theoretical and Near Infrared Modeling of Microfibril Angle

Abstract: SUMMARYA theoretical model was built predicting the relationship between microfibril angle and lignin content at the Angstrom (A) level. Both theoretical and statistical examination of experimental data supports a square root transformation of lignin to predict microfibril angle. The experimental material used came from 10 longleaf pine (Pinuspalustris) trees. Klason lignin (n=70), microfibril angle (n=70), and extractives (n=100) were measured and reported at different ring numbers and heights. All three trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…The researchers noted the innerwood contained a relatively higher amount (i.e., 5.2% to 7.0%) of alcohol-benzene extractives compared to the outerwood (i.e., 2.5% to 4.5%). Similar results where the extractives content of Pinus palustris decreased as one moved from the pith towards the bark, and also from the butt higher up the stem have been reported [34]. As can be seen in Table 4, the differences in the extractives content between the families on a site is a function of genotypic variation; whereas differences within a single family on the two sites is a response to environmental conditions such as the presence of biological degraders or silvicultural treatments that aim to increase tree growth [35,36].…”
Section: Prediction and Screening Of The Elite Loblolly Pine Familiessupporting
confidence: 83%
“…The researchers noted the innerwood contained a relatively higher amount (i.e., 5.2% to 7.0%) of alcohol-benzene extractives compared to the outerwood (i.e., 2.5% to 4.5%). Similar results where the extractives content of Pinus palustris decreased as one moved from the pith towards the bark, and also from the butt higher up the stem have been reported [34]. As can be seen in Table 4, the differences in the extractives content between the families on a site is a function of genotypic variation; whereas differences within a single family on the two sites is a response to environmental conditions such as the presence of biological degraders or silvicultural treatments that aim to increase tree growth [35,36].…”
Section: Prediction and Screening Of The Elite Loblolly Pine Familiessupporting
confidence: 83%
“…A larger increase in CV (13.0%-21.7%) was obtained from rings 5 to 20 of latewood fibres from the earlier study by Mott et al (2002) with the CV reaching 34.1% for growth ring 40 . Via et al (2007) reported a greater range of CVs (15%-55%) in a MFA study of 41-yearold longleaf pine trees, ranging from 15.7% (growth ring 4) to 55.8% (growth ring 16). It was noted that the GP258 earlywood calibration provided a slightly higher mean MFA (32.3°) than its latewood counterpart (30.9°).…”
Section: Multivariate Analysismentioning
confidence: 94%
“…In these studies, spectra were collected from the radial-longitudinal face of wooden strips cut from increment cores, and averaged over 10 mm increments, and as a consequence, it was not possible to follow the variation of MFA on an annual basis to observe the effects of silvicultural treatments. Inter-ring variability has been assessed by sectioning individual early wood and late wood rings from increment cores and collecting NIR spectra from the tangential face , Schimleck et al 2007, Via et al 2007, Hein et al 2010. Kelley et al (2004) obtained reasonable correlations with MFA from loblolly pine (Pinus taeda L.); however, only 72 total samples were used in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the increase in model robustness with nonlinear modeling supports the supposition that prediction of MOR with NIR spectra may be nonlinear in relation. This may be due to a) the nonlinear relationship between density and spectra (Via 2010 b) the nonlinear covariance between wood chemistry, Fibre morphology, age, and spectra that is apparent (Via et al 2007(Via et al , 2009) and c) the nonlinear relationship between microfibril angle and lignin with higher polymer angles resulting in increased plastic deformation in lignin just prior to Fibre rupture, which results in an apparent nonlinear relationship between microfibril angle and MOR for southern pine and Douglas-fir (Pseudotsuga menziesii var. menziesii [Mirb.]…”
Section: Nonlinear Pcr Modelingmentioning
confidence: 99%
“…The effect of genetic control or silvicultural response is also strong but more limited than age effects. NIR signals have been shown to be sensitive to various traits under genetic and silviculture control including lignin, cellulose, hemicellulose, extractives, microfibril angle, and density (Schimleck et al 2002, Perez et al 2007, Via et al 2007, Isik et al 2011. Via et al (2005a) demonstrated that tracheid length could be predicted with NIR but as a function of age.…”
Section: Introductionmentioning
confidence: 99%